2019
DOI: 10.1002/hrm.21958
|View full text |Cite
|
Sign up to set email alerts
|

All for one and one for all: A mechanism through which broad‐based employee stock ownership and employee‐perceived involvement practice create a productive workforce

Abstract: Drawing on social identity theory, this research frames a multimediational model that delineates how broad‐based employee stock ownership (BESO) and employee‐perceived involvement practice in tandem yield a productive workforce at the organization level. In our theoretical model, we propose that social cohesion and voluntary turnover are collective attitudinal and behavioral outcomes resulting from the shared perception of we‐ness that employees experience through both participatory practices. Our path analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 131 publications
(200 reference statements)
0
14
0
Order By: Relevance
“…Job satisfaction ----------------Organizational commitment Fig. 2 The three variables configuration of the present reasearch Most recently, Kim and Han (2019) proposed a path analysis using a multisource, time-lagged dataset of 176 US companies to study the link between participation and productivity. They showed empirically that employee ownership and decision-making participation are related to labor productivity.…”
Section: Trust In Managementmentioning
confidence: 99%
“…Job satisfaction ----------------Organizational commitment Fig. 2 The three variables configuration of the present reasearch Most recently, Kim and Han (2019) proposed a path analysis using a multisource, time-lagged dataset of 176 US companies to study the link between participation and productivity. They showed empirically that employee ownership and decision-making participation are related to labor productivity.…”
Section: Trust In Managementmentioning
confidence: 99%
“…Given the prevalence of these stock purchase plans, it is somewhat surprising that academic research seeking to answer questions about the impact of such plans on employees and employers has been slow to emerge. However, a recent special issue of Human Resource Management is an indication of increasing scholarly interest in the topic (Basterretxea, Heras‐Saizarbitoria, & Lertxundi, ; Kang & Kim, ; Kim & Han, ). Despite these recent advancements, very little is known about the determinants of an employee's decision to participate in a stock purchase plan and the inherent risk borne by employees.…”
Section: Introductionmentioning
confidence: 99%
“…In their study entitled “All for one and one for all: A mechanism through which broad‐based employee stock ownership and employee perceived involvement practice create a productive workforce,” Kim and Han () develop a multi‐mediational model that describes how BESO affects organizational labor productivity. Specifically, they argue that the BESO‐labor productivity relationship is not direct but is instead mediated by attitudinal and behavioral outcomes (i.e., social cohesion and voluntary turnover).…”
mentioning
confidence: 99%
“…Ren et al () found that executive stock ownership weakened the relationship between BESO and firm performance in the Chinese context, as the employees perceive their incentives relative to the executives as being inequitable. With BESO and employee involvement practices having already been linked within this domain, Kim and Han () sought to further explore the nature of this interaction for various firm‐level outcomes. They found that employee involvement directly enhanced BESO with respect to labor productivity, but these activities substituted for each other when it came to social cohesion and, subsequently, voluntary turnover.…”
mentioning
confidence: 99%
See 1 more Smart Citation